2021
DOI: 10.1074/jbc.ra120.015876
|View full text |Cite
|
Sign up to set email alerts
|

Elongin A regulates transcription in vivo through enhanced RNA polymerase processivity

Abstract: Elongin is an RNA polymerase II (RNAPII)-associated factor that has been shown to stimulate transcriptional elongation in vitro . The Elongin complex is thought to be required for transcriptional induction in response to cellular stimuli and to ubiquitinate RNAPII in response to DNA damage. Yet, the impact of the Elongin complex on transcription in vivo has not been well studied. Here, we performed comprehensive studies of the role of Elongin A, the largest subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…ELOA was originally identi ed as a transcriptionally active subunit of RNA polymerase II (Pol II) transcription factor Elongin (SIII), which stimulates the overall rate of Pol II elongation through direct interactions with the enzyme [25,26]. Elongin is composed of ELOA and a heterodimeric submodule comprised of Elongin B and C proteins, which bind to a short ELOA sequence motif referred to as the BC box that has potent transcriptional regulation activity [27]. Inaddition to being a part of SIII, ELOA also functions as the substrate recognition subunit of a Cullin-RING E3 ubiquitin ligase that ubiquitinates theRPB1 subunit of Pol II in response to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…ELOA was originally identi ed as a transcriptionally active subunit of RNA polymerase II (Pol II) transcription factor Elongin (SIII), which stimulates the overall rate of Pol II elongation through direct interactions with the enzyme [25,26]. Elongin is composed of ELOA and a heterodimeric submodule comprised of Elongin B and C proteins, which bind to a short ELOA sequence motif referred to as the BC box that has potent transcriptional regulation activity [27]. Inaddition to being a part of SIII, ELOA also functions as the substrate recognition subunit of a Cullin-RING E3 ubiquitin ligase that ubiquitinates theRPB1 subunit of Pol II in response to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the CSB-Elongin ubiquitin ligase could safeguard inducible RNAPII transcription by ensuring expeditious removal of stalled RNAPII from genes. In addition, a very recent study revealed that Elongin A depletion leads to a substantial decrease in phosphorylation of the RNAPII CTD on serine 2, suggesting it can contribute to the maturation of RNAPII elongation complexes (41). Together, contributions of Elongin and the Elongin ubiquitin ligase in each of these processes could contribute to the modest delay in RNAPII accumulation on genes seen in mouse cells lacking Elongin A.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…Our observation that mouse cells lacking Elongin A exhibit a marked delay in removal of RNAPII from glucocorticoid-induced genes following withdrawal of hormone argues that the CSB-Elongin pathway makes an important contribution to rapid changes in transcription rates in response to changing levels of signaling molecules, perhaps via removal of RNAPII by ubiquitin-dependent proteolysis following RNAPII ubiquiqitylation by the Elongin J o u r n a l P r e -p r o o f ubiquitin ligase. Alternatively, since Elongin stimulates the rate of transcript elongation in vitro, the delay in loss of RNAPII from genes in Elongin A-deficient cells following hormone withdrawal could, in principle, be due to decreased rates of elongation; however, two recent reports indicating that overall RNAPII elongation rates in cells lacking Elongin A are not dramatically changed argue against this model (41,42). Finally, it is important to note that we Technologies), 100 U/ml of penicillin, and 100 μg/ml of streptomycin (Gibco, Life Technologies).…”
Section: Summary and Perspectivementioning
confidence: 99%
“…Furthermore, in vitro studies demonstrated that Elongin A stimulates the elongation step of transcription ( Conaway and Conaway, 1999 ). Recent genome-wide analysis of Elongin A-deficient cells did not reveal strong defects in overall Pol II transcription elongation rates but showed increased accumulation of Pol II at TSSs, suggesting that Elongin A regulates the transition from pause to transcription elongation ( Ardehali et al, 2020 ; Wang et al, 2020 ). Interestingly, the genome-wide occupancy data suggest that Elongin A is preferentially recruited to sites upstream of the TSS and to enhancer elements.…”
Section: Tfii-i Regulates the Transition From Transcription Pausing To Elongationmentioning
confidence: 99%
“…This could indicate that Elongin A is recruited by sequence-specific transcription activators that bind promoters and/or enhancers. Furthermore, RNA-seq data show that Elongin A deficiency only affects the expression of a small set of genes ( Ardehali et al, 2020 ; Wang et al, 2020 ).…”
Section: Tfii-i Regulates the Transition From Transcription Pausing To Elongationmentioning
confidence: 99%